1994
DOI: 10.1002/j.1460-2075.1994.tb06435.x
|View full text |Cite
|
Sign up to set email alerts
|

The Saccharomyces cerevisiae APS1 gene encodes a homolog of the small subunit of the mammalian clathrin AP-1 complex: evidence for functional interaction with clathrin at the Golgi complex.

Abstract: Clathrin‐associated protein (AP) complexes have been implicated in the assembly of clathrin coats and the selectivity of clathrin‐mediated protein transport processes. We have identified a yeast gene, APS1, encoding a homolog of the small (referred to herein as sigma) subunits of the mammalian AP‐1 complex. Sequence comparisons have shown that Aps1p is more similar to the sigma subunit of the Golgi‐localized mammalian AP‐1 complex than Aps2p, which is more related to the plasma membrane AP‐2 sigma subunit. Lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
92
0
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 72 publications
10
92
0
1
Order By: Relevance
“…7A). A portion of Kex2p also coeluted with Chc1p and Aps1p, consistent with a role for clathrin coats in the localization of Kex2p to the TGN as reported previously (21). Electron microscopy of samples negatively stained with uranyl acetate confirmed the presence of clathrin-coated vesicles in these fractions (data not shown).…”
Section: Clc1p Is Required For Efficientsupporting
confidence: 89%
“…7A). A portion of Kex2p also coeluted with Chc1p and Aps1p, consistent with a role for clathrin coats in the localization of Kex2p to the TGN as reported previously (21). Electron microscopy of samples negatively stained with uranyl acetate confirmed the presence of clathrin-coated vesicles in these fractions (data not shown).…”
Section: Clc1p Is Required For Efficientsupporting
confidence: 89%
“…Further insights into evolutionary relationships can be obtained by looking for homologues of the AP subunits in lower eukaryotes. In the budding yeast S. cerevisiae, in which the entire genome is known, genes have been identified that encode subunits sufficient to form three complete AP complexes, and there is strong genetic and biochemical evidence that yeast has AP-1 and AP-3 complexes that are functionally equivalent to AP-1 and AP-3 in mammals (Phan et al, 1994;Rad et al, 1995;Stepp et al, 1995;Cowles et al, 1997;Panek et al, 1997). It has been proposed that yeast also has an AP-2 complex, because the remaining AP subunits in yeast are more homologous to mammalian AP-2 subunits than to the subunits of any of the other AP complexes , including AP-4.…”
Section: Discussionmentioning
confidence: 99%
“…At time points indicated for Ste3p and at 30 min of chase for ␣-factor maturation, 0.5 OD 600 in 200 l were transferred to tubes containing sodium fluoride and sodium azide (10 mM final). Immunoprecipitation of ␣-factor and cell lysis and immunoprecipitation of Ste3p were performed as described (31,32). For pulse-chase immunoprecipitations of ALP, CPS, and ␣-factor, cells were treated as above, except that in the case of ALP cells were labeled for 5 min and in all cases the chase was initiated by addition of 1:10 volume of 2% yeast extract, 0.3% cysteine, and methionine.…”
Section: Methodsmentioning
confidence: 99%